Delignification of empty fruit bunch (EFB) using low transition temperature mixtures (LTTMs): A review - Loong, Y.C. (Trans Tech Publications Ltd, 2014)
Biomass processing using low transition temperature mixtures (LTTMs) has the potential to become a sustainable alternative resource for production of raw materials and fuels with a neutral carbon dioxide balance. The state of art for customizing the physicochemical behaviour of these new green solvents by a prudent selection of the constituentsâ nature and ratio through microwave irradiation is presented in this work. The impact of the following parameters, namely type of malic acid, molar ratio of malic acid to natural salt, water content and temperature of treatment are related to the solvation behaviour of LTTMs. An overview of the conditions for the highest efficiency in the delignification of empty fruit bunch (EFB) are described. Â© 2014 Trans Tech Publications, Switzerland.